Heyde syndrome as a presentation of acquired Von Willebrand syndrome: what the gastroenterologist should know. - Córdoba Guzmán, Andrea Carolina; castroDaza , Erlison Mauricio (Jour Med Resh and Health Sci, 2022)
Heyde syndrome was first described in 1958 by Dr. Eward C. Heyde who sent a letter to the editor of The New England Journal Of Medicine describing a series of 10 cases of patients whom all had in common the presence of aortic stenosis and frequent gastrointestinal bleeding (1). Nevertheless it wasn’t until 28 years later that the cause of the gastrointestinal bleeding in these patients was documented, which was related to the presence of angiodysplasias (2). Subsequent observations in different clinical studies reported the healing of the bleeding in these patients after aortic valve replacement, suggesting a cause-effect relationship between these two clinical entities and laid the first foundations in the pathophysiology of the disease, by finding alterations in the concentrations of von Willebrand factor multimers, thus explaining the predisposition to bleeding in these patients, due to defects in primary hemostasis. This is how Heyde syndrome is currently considered, as an acquired type 2 von Willebrand syndrome (AVWS Type 2), and different proposals in the treatment have been made in which comprehension of the main pathophysiological mechanism of the disease, aortic valve replacement remains the best treatment option(3). In this document we will review the pathophysiological bases of the disease, its presentation and treatment options.